Erbium-doped borosilicate glasses containing various amounts of P2O5 and Al2O3: Influence of the silica content on the structure and thermal, physical, optical and luminescence properties. (October 2015) - Bourhis, Kevin; Massera, Jonathan; Petit, Laeticia; Koponen, Joona; Fargues, Alexandre; Cardinal, Thierry; Hupa, Leena; Hupa, Mikko; Dussauze, Marc; Rodriguez, Vincent; Ferraris, Monica
Graphical abstract: Highlights: Er 3+ doped borosilicate glasses were processed with different compositions and characterizations. An increase in the SiO2 content leads to a silicate-rich environment around the Er 3+ site. An increase in the SiO2 content decreases the Er 3+ absorption cross-section at 980 nm. Glasses with 60 mol% of SiO2 exhibit a stronger emission intensity at 1530 nm than glasses with x  = 50. Highest 1.5 μm emission intensity was achieved for the Al and P containing glass with 60 mol% of SiO2 . Abstract: The influence of the silica content on several properties of Er-doped borosilicate glasses in the presence of various amounts of P2 O5 and Al2 O3 has been investigated. The introduction of P2 O5 and/or Al2 O3 are responsible for structural modifications in the glass network through a charge-compensation mechanism related to the formation of negatively-charged PO4 and AlO4 groups or through the formation of AlPO4 -like structural units. In this paper, we show that an increase in the SiO2 content leads to a silicate-rich environment around the Er 3+ site, resulting in an increased dependence of the Er 3+ ions optical and luminescence properties on the P2 O5 and/or Al2 O3 concentration. The highest emission intensity at 1.5 μm was achieved for the glass with an equal proportion of P and Al in the glass system with 60 mol% of SiO2 .